(untitled) (Journal of Science and Technology, 2016)
The magnetic, electronic (reflectance) and infrared spectral properties of divalent metal complexes, [M(N-ATB)3] SO, and [Cu(N-ATB),]SO, (where M = Mn, Fe, Co, Ni and Zn; N-ATB = N-Acetylthiobenzamide are reported. Substitution of a methyl group in place of a phenyl one in N-Benzoylthiobenzsmide is found to weaken the C= 0 and C=S; and strengthen the N-H bonds of the metal chelate ring. Out of the two -n- - (C = 0 and C=S) transitions, the thiocarbonyl one shows stronger interaction in the metal complexes. The values of the magnetic moments are similar to those of analogous metal chelates.